Extreme weather : forty years of the Tornado and Storm Research Organisation (TORRO) - Doe, Robert (John Wiley & Sons Inc., 2016)
"This book will be aimed primarily at researchers in the field of meteorology and climatology looking for a reference to extreme weather in the UK."--Provided by publisher.